RUDIMENTARY RESEARCH ON THE UNIVERSAL DESIGN OF URBAN SPATIAL INFORMATION CONSIDERING THE BEHAVIOR OF FOREIGNERS - J. Ge; K. Hokao (Lowland Technology International, 2005)
Some rudimentary researches on the design of urban spatial information from the viewpoint of foreigners were performed through the case study of Saga City, Japan. By means of questionnaire survey, on-site investigation and route-searching experiment, the present condition, especially the problems of the urban spatial information for the behavior of foreigners were analyzed and grasped, and some principles of the design of urban spatial information considering the behavior of foreigners were proposed, which could be regarded as the extension of the concept of universal design. The results of the research can not only provide the basic data for the design and improvement of urban spatial information, but also can help to enlarge the concept of universal design by considering the factor of foreigners in wider fields.